Socio-Psychological Analysis Of Anxiety In The Era Of Globalization - Tokhir Kurbonov (Peerian Journals Publishing, 2024)
Psychoanalytic approach. One of the first who made an attempt to explain the nature of anxiety was S. Freud. According to Freud's teachings, certain experiences that have taken place in a person's life: actions, impulses, thoughts or memories that are excruciatingly painful or generate severe anxiety are repressed from consciousness, and those forces that led to the repression of what happened from memory are mobilized, preventing their restoration in consciousness
Keywords: Psychoanalytic; approach; preventing